The Carbon Footprint of Medical Procedures: Drivers, Emissions, and Decarbonization Strategies (London Journal of Research In Science: Natural and Formal, 2025)
The global healthcare sector, paradoxically, stands as a significant contributor to the very climate crisis it aims to mitigate. Estimates suggest that healthcare accounts for a substantial portion of global greenhouse gas (GHG) emissions, ranging between 4% and 10% of total worldwide emissions, and approximately 8.5% within the United States.1 This impact directly contradicts the fundamental medical principle of "do no harm," as climate change itself poses a major and escalating threat to human health. Medical procedures, particularly those conducted within energy-intensive operating rooms (ORs), are identified as primary drivers of these emissions. Key contributors include the disproportionately high energy consumption of ORs, which can be up to six times greater than that of standard clinical wards, the pervasive use of potent Anaesthetic gases, the widespread adoption of single-use medical devices and consumables, and the often-overlooked yet significant carbon footprint associated with patient and staff travel.3 Effective strategies for reducing these emissions necessitate a multi-faceted approach. This includes optimizing operational energy use within facilities, transitioning towards reusable medical devices, implementing robust reprocessing programs for single-use devices, adopting Anaesthetic agents with lower global warming potential (GWP), enhancing comprehensive waste management practices, leveraging telehealth services to reduce travel, and integrating sustainable principles into procurement policies. These strategic shifts not only contribute to environmental stewardship but frequently result in considerable economic benefits through cost savings.8 Achieving net-zero healthcare demands a systemic transformation, embedding sustainability into every layer of decision-making, from individual clinical actions to overarching national policy frameworks. This report elaborates on these critical drivers and outlines a comprehensive set of strategies to mitigate healthcare's environmental impact.